Fossils - McDougall, Jill (Pearson Education, Dorling Kindersley Australia, 2010)
"Fossils" by Jill McDougall explores the fascinating world of fossils, detailing their formation, types, and significance in understanding Earth's history. Through engaging explanations and vivid illustrations, the book invites readers to discover how fossils provide clues about ancient life and the evolution of species.